Laboratory-fabricated, Acrylic Resin Cylinders for Fixed, Provisional Implant Restorations - Flavio H. Rasetto, Od, BDS,1 Carl F. Driscoll, DMD,2 and Lafeyette Hawkes3 (Journal of Prosthodontics, 2000)
DURING THE various stages of fabricating crowns and fixed dentures, the correct manipulation of many different materials is required. One area involves application of die spacer in the appropriate thickness to the die. The recommended thickness is 20 to 30 microns.1,2 (Acetone is periodically added to maintain the proper viscosity of the die spacer as its volatility is quite high.) Insufficient management of die spacer may cause inaccuracies that result in an incomplete seating of the crown during insertion.